9x(y+4)-10(y+4)
(9x-10)(y+4)
Answer:
Option C
Step-by-step explanation:
complete question
A. 35[3]6cB. 12[3]12cC. 12[3]6cD.72c
The given equation can be written as
5^3√6c+7^3√6c
5 *
+ 7 * ![\sqrt{3 *3*2c}](https://tex.z-dn.net/?f=%5Csqrt%7B3%20%2A3%2A2c%7D)
5 * 3 *
+ 7 * 3 *![\sqrt{2c}](https://tex.z-dn.net/?f=%5Csqrt%7B2c%7D)
15 *
+ 21 *![\sqrt{2c}](https://tex.z-dn.net/?f=%5Csqrt%7B2c%7D)
36 *![\sqrt{2c}](https://tex.z-dn.net/?f=%5Csqrt%7B2c%7D)
12 [3]*![\sqrt{2c}](https://tex.z-dn.net/?f=%5Csqrt%7B2c%7D)
Option C is correct
I will help if you post a picture or something
The GCF is what they all have in common.
2x is the only thing they ALL share.